Konseling Kelompok Teknik Cognitive Behavior Therapy Dalam Mengelola Stres Akademik Santri Beasiswa di Pesantren - Wulandari, Nila; Hermatasiyah, Nur; Setiyadi, Desi (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This study aims to analyze the application of group counseling with Cognitive Behavioral Therapy (CBT) techniques in helping students manage academic stress at the Tahfizh Daarul Qur'an Takhassus Cikarang Islamic Boarding School. The academic pressure faced by students is caused by various factors, including the demands of meeting the target of memorizing the Qur'an, difficulty in memorizing, and a busy schedule of activities. This study uses a qualitative descriptive method with data collection techniques through interviews, observations, and documentation. The qualitative descriptive approach provides an in-depth understanding of changes in students' mindsets, emotions, and coping strategies after participating in the CBT group counseling intervention. The results showed that 5 students experienced academic stress levels, characterized by low motivation to memorize and anxiety about memorization targets. The results showed that after participating in the CBT group counseling session, students experienced a decrease in academic stress levels, increased awareness in managing negative thoughts, and the development of skills in dealing with academic pressure more positively. Around 85% of students reported that they felt calmer and less burdened when facing academic stress, compared to before participating in counseling. The results of this study indicate that group counseling using CBT techniques plays a role in helping students understand and manage academic stress through a more systematic approach. Thus, this method can be a reference in developing guidance and counseling services in Islamic boarding schools to improve psychological well-being and student learning motivation